If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying W + -6 = 10 Reorder the terms: -6 + W = 10 Solving -6 + W = 10 Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + W = 10 + 6 Combine like terms: -6 + 6 = 0 0 + W = 10 + 6 W = 10 + 6 Combine like terms: 10 + 6 = 16 W = 16 Simplifying W = 16
| K+10=30 | | H(t)=-16t^2+48t+50 | | 5+8p=-147 | | t^3-4t^2+7t+3=0 | | 5+8-p=-147 | | M+-10=10 | | 4x+20=3x+6 | | 9s-44=2s+5 | | 48+8y=16y+16 | | 9x+6(100)=7x+700 | | (q+33)+6q=180 | | M+-5=-10 | | z+12=5z | | 92=x(x+4) | | a^4b^6/ab^3 | | 5/8x-51/8x=3/2 | | 9x+6(100)= | | 3q-r=7 | | 483575.32=19105.8019x^(5/2)-60446.915x | | 2=9y/4 | | 18=(4/3x)(-3/2x) | | 5/4=z/8 | | 8+6(x-3)=2-7(x-6) | | 4x*2x^2=0 | | 5/4=2/8 | | 20x-(2x-4)=40 | | (4x+7)+(2x-1)=180 | | K-7=-9 | | 3(1-2x)=2(5x-1) | | 5x+20=4x+20 | | 14+6=-4(4x-5) | | 4x-12-3x+9=2x+8 |